2013
DOI: 10.1016/j.neuropsychologia.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Altered visual–spatial attention to task-irrelevant information is associated with falls risk in older adults

Abstract: Executive cognitive functions play a critical role in falls risk -a pressing health care issue in seniors. In particular, intact attentional processing is integral for safe mobility and navigation. However, the specific contribution of impaired visual-spatial attention in falls remains unclear. In this study, we examined the association between visual-spatial attention to task-irrelevant stimuli and falls risk in community-dwelling older adults. Participants completed a visual target discrimination task at fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 51 publications
(66 reference statements)
5
19
0
Order By: Relevance
“…They also suggested that visual dysfunction, is not a single sensory problem, but may be more complex than this and can contribute to falls through a number of different mechanisms. This is consistent with findings of Nagamutsu et al [57] who noted altered visual-spatial attention to taskirrelevant information was associated with heightened falls risk among older adults.…”
Section: Vision and Fallssupporting
confidence: 93%
“…They also suggested that visual dysfunction, is not a single sensory problem, but may be more complex than this and can contribute to falls through a number of different mechanisms. This is consistent with findings of Nagamutsu et al [57] who noted altered visual-spatial attention to taskirrelevant information was associated with heightened falls risk among older adults.…”
Section: Vision and Fallssupporting
confidence: 93%
“…Such measures are important, due to the potentially negative consequences of misjudging our environment, for example colliding with objects. This could be particularly consequential for older adults, because impaired lateral spatial processing has been associated with an increased risk of falls [ 14 , 16 ]. In contrast to lab-based measures, these ‘real-world’ tasks have, by-and-large, identified systematic behavioural errors and preferences towards the right side of space.…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that males and females may produce differential patterns of pseudoneglect over aging, with older females exhibiting more consistent left biases, whilst older males may exhibit a drift into rightward bias with age (Varnava & Halligan, 2007;Chen, Goedert, Murray, Kelly, Ahmeti, Barrett, 2011). Meanwhile there is evidence for reduced lateral bias in older participants in lateralised visual detection tasks (Learmonth, Thut, Benwell & Harvey, 2015;Nagamatsu, Carolan, Liu-Ambrose & Handy, 2011;Nagamatsu, Munkacsy, Liu-Ambrose & Handy, 2013).…”
Section: Introductionmentioning
confidence: 99%